Children's Literature of the English Renaissance - Wooden, Warren W. (Book collections on Project MUSE., 1986)
Warren W. Wooden's pioneering studies of early examples of children's literature throw new light on many accepted works of the English Renaissance period. In consequence, they appear more complex, significant, and successful than hitherto realized. In these nine essays, Wooden traces the roots of English children's literature in the Renaissance beginning with the first printed books of Caxton and ranging through the work of John Bunyan. Wooden examines a number of works and authors from this period of two centuries -- some from the standard canon, others obscure or neglected -- while addressin.